Piezoactive amino acid derivatives containing fragments of planar-chiral ortho-carboranes. Issue 32 (16th July 2018) - Gruzdev, Dmitry A.; Nuraeva, Alla S.; Slepukhin, Pavel A.; Levit, Galina L.; Zelenovskiy, Pavel S.; Shur, Vladimir Ya.; Krasnov, Victor P.
Abstract : Compounds possessing a high piezoelectric activity have been found among enantio pure ortho -carboranyl derivatives of amino acids. Abstract : A series of novel ( S )-amino acid derivatives bearing planar-chiral (3-acylamino-1, 2-dicarba- closo -dodecaboran-1-yl)acetyl substituents was synthesized. Carboranyl amino esters were obtained in a diastereomerically pure form (according to chiral HPLC). Single crystals of individual diastereomers were studied by optical microscopy, X-ray diffraction analysis and piezoresponse force microscopy. The piezoelectric activity of some compounds was shown to exceed that of most known organic piezoelectrics.